Diagnostic Utility of Diffusion-Weighted Imaging and Apparent Diffusion Coefficient for Common Orbital Lesions: A Review. Issue 6 (November 2022) - Cameron, Cassie A.; Tong, Jessica Y.; Juniat, Valerie; Patel, Sandy; Selva, Dinesh
Abstract : Purpose: To review and summarize the existing literature surrounding the clinical use of diffusion-weighted imaging and apparent diffusion coefficient (ADC) as diagnostic tools in differentiating common orbital lesions. Methods: A systematic literature review on the use of ADC and diffusion-weighted imaging sequences for orbital imaging was performed. Only original research articles that reported ADC values for benign or malignant lesions were included. Results: Malignant orbital tumors have an overall lower mean ADC value than benign masses. Orbital lymphoma is characterized by consistently lower ADC values compared with other malignant orbital masses; a threshold value less than 0.775 × 10 −3 mm 2 /s has been proposed to distinguish orbital lymphoma from other neoplastic and non-neoplastic orbital masses. To differentiate orbital inflammatory disease from lymphoma, an ADC threshold greater than 0.92 × 10 −3 mm 2 /s has been proposed. Conclusions: Orbital masses encompass a host of benign and malignant etiologies and can present a diagnostic challenge on both clinical and radiological assessment. Recent advanced MRI techniques such as diffusion-weighted imaging and ADC can improve the diagnostic specificity for orbital disease, particularly in differentiating benign from malignant lesions and lymphoma from orbital inflammatory disease. Abstract : Diffusion-weighted imaging and apparent diffusion coefficient are advanced magnetic resonance imaging sequences that have a role in characterizing common orbital lesions, including differentiating benign from malignant tumors and lymphoma from orbital inflammatory disease.